PAIN MANAGEMENT OF SENSORIMOTOR POLYNEUROPATHY IN COVID-19 INFECTIONS - Lucic Prokin, aleksandra; Šekarić, Jelena; Krtinić, Dane (Acta medicae Medianae, 2023)
A 73-year-old man has tested positive for SARS-CoV-2. On the tenth day of the disease, a symmetrical distribution of spontaneous pain and dysesthesia occurs in both feet. Initial pain management, ordered by general practitioner was not effective, so he was referred to the pain specialist. The new therapy included combination of anticonvulsants, antidepressants and adjuvant therapy with partial, but satisfactory reduction in pain. Education/reeducation of general practitioners would accelerate the detection and symptomatic treatment in the early stages of COVID-19. An even better suggestion would be to refer these patients to pain medicine specialists.